2013
DOI: 10.3109/13625187.2013.835394
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use and method among immigrant women in France: Relationship with socioeconomic status

Abstract: Our findings suggest the need to advance our understanding of potential barriers to contraceptives created by socioeconomic forces across different societal/cultural contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
7
24
1
Order By: Relevance
“…One study in France compared self‐reported user rates of contraceptives between immigrants and natives, and several studies have compared user rates of contraceptives only among women undergoing induced abortion . Our results showing lower contraceptive use among immigrants are consistent with the findings from these studies . The association between higher socio‐economic status and use of contraceptives in a general population is well established .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One study in France compared self‐reported user rates of contraceptives between immigrants and natives, and several studies have compared user rates of contraceptives only among women undergoing induced abortion . Our results showing lower contraceptive use among immigrants are consistent with the findings from these studies . The association between higher socio‐economic status and use of contraceptives in a general population is well established .…”
Section: Discussionsupporting
confidence: 88%
“…Copper IUDs are still used, though not registered in the Norwegian Prescription Database. However, based on figures from drug wholesalers, copper IUDs only constituted 27% of all IUDs sold in Norway in 2008, and our findings are consistent with a recent study that included information on IUDs . Thirdly, both IUDs and implants are typically used for several consecutive years and overall use is therefore underestimated in this study, but this underestimation would apply for both natives and immigrants.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As in other Western Europe countries, a large proportion of women living with HIV in France are migrants from sub-Saharan Africa with a lower use of contraceptive methods compared to French natives [14,15]. This article documents the contraceptive methods and associated variables for women living with HIV in France, with a specific focus upon women from sub-Saharan Africa relative to other women (mainly native French women).…”
Section: Introductionmentioning
confidence: 99%
“…It aims to assess the extent to which this pattern is related to HIV infection characteristics, to reproductive and sexual factors, to social situations [13,14] and to accessibility to reproductive health services.…”
Section: Introductionmentioning
confidence: 99%